2023
DOI: 10.1007/s43465-023-00887-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Self-Reported Function, Functional Tests and Biomechanical Parameters in Patients 12 Months After Total Hip Arthroplasty: A Preliminary Cross-Sectional Study

Abstract: Background/Purpose Several methods are used to evaluate the outcome of total hip arthroplasty (THA), however, their relationship at different time points after surgery is unclear. The purpose of this exploratory study was to investigate correlations between self-report function, performance-based tests (PBTs) and biomechanical parameters in patients 12 months after THA. Methods Eleven patients were included in this preliminary cross-sectional study. Hip di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
4
3
0
Order By: Relevance
“…On the other hand, a lower level of hip pain interference in usual work/housework (item 12) was linked to a slower cadence. Our findings support previous studies in which self-reported outcomes and biomechanical parameters were correlated in post-THA patients 12 months post-THA [ 21 , 22 ]. In the study of John et al [ 21 ], the Hip Disability and Osteoarthritis Outcome Score (HOOS) correlated strongly with hip strength, while the correlations with step length asymmetry and contact time asymmetry were not significant and relatively weak (r < 0.32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, a lower level of hip pain interference in usual work/housework (item 12) was linked to a slower cadence. Our findings support previous studies in which self-reported outcomes and biomechanical parameters were correlated in post-THA patients 12 months post-THA [ 21 , 22 ]. In the study of John et al [ 21 ], the Hip Disability and Osteoarthritis Outcome Score (HOOS) correlated strongly with hip strength, while the correlations with step length asymmetry and contact time asymmetry were not significant and relatively weak (r < 0.32).…”
Section: Discussionsupporting
confidence: 92%
“…Secondary outcomes included potential correlations between postoperative spatiotemporal and demographic/clinical characteristics relating to patients’ functionality. Based on previous relevant studies on post-THA patients [ 21 , 22 ], we hypothesized that postoperative spatiotemporal characteristics have the same trend with patient-reported outcomes. Biomechanists and rehabilitation experts could utilize such evidence to advance the development of targeted rehabilitation programs that ultimately improve the functional capacity of patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a lower level of hip pain interference in usual work/housework (item 12) was linked to a slower cadence. Our findings support previous studies in which self-reported outcomes and biomechanical parameters were correlated in post-THA patients 12 months post-THA [38,39]. In the study of John et al [38], the Hip Disability and Osteoarthritis Outcome Score (HOOS) correlated strongly with hip strength, while the correlations with step length asymmetry and contact time asymmetry were not significant and relatively weak (r < 0.32).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings support previous studies in which self-reported outcomes and biomechanical parameters were correlated in post-THA patients 12 months post-THA [38,39]. In the study of John et al [38], the Hip Disability and Osteoarthritis Outcome Score (HOOS) correlated strongly with hip strength, while the correlations with step length asymmetry and contact time asymmetry were not significant and relatively weak (r < 0.32). In the study of Bolink et al [39], moderate to strong significant correlations were found between the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and walking speed, cadence, and step time (0.31 > r <0.51).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation